VEGFR‐2 is downregulated in sestamibi‐negative parathyroid adenomas. Issue 10 (10th July 2019) - Erovic, Boban M.; Goldstein, David P.; Asa, Sylvia L.; Janik, Stefan; Mete, Ozgur; Irish, Jonathan C.
Abstract: Background: The purpose of this study was to determine the expression profile of several biomarkers in sestamibi‐positive ( n = 23) and sestamibi‐negative ( n = 6) parathyroid adenomas. Methods: A tissue microarray of parathyroid adenomas from 29 patients was constructed and slides were stained for several proteins involved in angiogenesis, inflammation, cell adhesion, cell cycle, apoptosis, and with markers of the sonic hedgehog, mTOR, Forkhead box O and WNT signal transduction pathways. Protein expression was determined using an image‐analysis software (Spectrum Plus©, 38 Aperio). Results: Protein expression analysis revealed that the vascular endothelial growth factor receptor 2 (VEGFR2) score was significantly higher in the sestamibi‐positive cohort compared to sestamibi‐negative adenomas ( P = .038). Other proteins were not differentially expressed between sestamibi‐positive and sestamibi‐negative adenomas. Conclusion: It is hypothesized that VEGFR‐2 overexpression in parathyroid adenomas increases vascular permeability resulting in a higher uptake of sestamibi.